The Brazilian catira: identities and rationalities - Palhares, José Vitor; Couto, Felipe Fróes; Carrieri, Alexandre de Pádua (Acta Scientiarum. Human and Social Sciences, 2018)
The free exchange, trade or catira is still an important form of circulation of goods in various communities of Brazil. However, its practitioners and all practical knowledge are still marginalized in management studies, under the justification that these practitioners would be amateurs, devoid of rationality and technical knowledge. This paper analyzes the identity construction of Brazilian catireiros to understand what types of rationality guide their trading practices. To this end, we interviewed 31 traders currently residing in Triângulo Mineiro and Alto Paranaíba regions, and the data collected were analyzed through French Discourse Analysis. The research pointed out that catireiros initially sought to identify and distinguish themselves from others using nouns, hence demonstrating who they are. Subsequently, the respondents used verbs that characterize their everyday catira practices, hence demonstrating what they are. In this sense, actions such as establishing contacts, getting to know people, negotiating, and understanding the market are some practices that constitute, (re)construct, and materialize the daily identities of such workers. It is also important to highlight that catireiros can also exercise different types of rationalities in different social contexts and although many have not achieved higher education, they should not have their trading practices delegitimized by the academia, since it is from these practices that they live, raise their families, and expand their business.